Addressing Health Care Disparities: A Radical Perspective and Proposal - Light, Donald W. (Frontiers in Sociology, 2020)
This paper begins by rethinking the sociological theory that social conditions are fundamental causes of health disparities and that controlling disease ironically increases or creates them. While usually true, the radical proposal of non-profit health care and pharmaceutical development could ameliorate health disparities if a nation or region like the EU looked to radically different but successful models such as the Drugs for Neglected Diseases initiative. It uses what could be called entrepreneurial collaboration for public health markets and inverts intellectual property, or public health IP to maximize health gain instead of profits.